(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
The article explores the impact of the Internet of Things (IoT) on marketing strategies and customer data management. The key aspects of using IoT data for personalization, targeting and omnichannel marketing are discussed, as well as issues of data privacy and security. Practical examples of successful IoT applications in various business sectors are given.